STRATEGI PUBLIC RELATION TAREKAT QODARIAH WA NAQSABANDIYAH DALAM MENSOSIALISASIKAN EKSISTENSI TAREKAT DI KECAMATAN SAMBAS - Halim Setiawan (Syi’ar: Jurnal Ilmu Komunikasi, Penyuluhan dan Bimbingan Masyarakat Islam, 2020)
Tarekat is the path or method that must be taken by a salik (traveler) to God, namely by purifying himself so that he can get as close as possible to Allah SWT. Taraket Qadiriyah wa Naqsybandiyah is a da'wah movement that teaches Islamic teachings in the process of getting closer to Allah SWT. This tarekat is a form or way of communicating religious teachings to the community. The spread of the Qadiriyah Wa Naqsyabandiyah Order in Sambas District is not so fast/busy, compared to Java and other areas. The most dominant cause of the lack of socialization of the teachings of the Qadiriyah Wa Naqsabandiyah tarekat here is that it does not spread through educational institutions such as Islamic boarding schools as is the case in Java. The media of its spread in the Sambas area only centered on houses and mosques so that it was only spread among ordinary people on a limited scale. The dissemination of information related to various activities, both socialization and routine Islamic studies, cannot be separated from the so-called Public Relations (PR). Every activity and place of activity is regulated by the TQN public relations department. Providing information is not only conveyed by one person but information received by each member is disseminated directly to the public. The existence of public relations in TQN is very helpful in every TQN activity that is carried out in Sambas District. Islamic studies and dhikr which are carried out in Sambas District are carried out every Wednesday night twice a month. Since the foundation was formed, the management together with the congregation has been aggressively socializing dhikr and science assembly activities carried out by the TQN Khathibiyah Sambas Foundation, both through Social Media, Stickers, Lathifah Diagrams, and Books assisted by the TQN public relations department.